Gauge invariance, background fields and modified ward identities - Freire, Filipe; Litim, Daniel F.; Pawlowski, Jan M. (International journal of modern physics. A, Particles and fields, gravitation, cosmology, 2001)
In this talk the gauge symmetry for Wilsonian flows in pure Yang-Mills theories is discussed. The background field formalism is used for the construction of a gauge invariant effective action. The symmetries of the effective action under gauge transformations for both the gauge field and the auxiliary background field are separately evaluated. Modified Ward-Takahashi and background field identities are used in my study. Finally it is shown how the symmetry properties of the full theory are restored in the limit where the cut-off is removed.